Cord blood gas results of pregnancies complicated by preeclampsia and the relationship of these results with the amount of proteinuria. Issue 4 (25th January 2021) - Demir, Ömer; Sal, Hidayet; Ozalp, Mirac; Aran, Turhan; Osmanağaoğlu, Mehmet A.
Abstract: Aim: To evaluate whether there is a statistically significant difference between the cord blood gas parameters of pregnancies complicated with preeclampsia and uncomplicated pregnancies and to show whether the amount of proteinuria affects fetal cord blood gas parameters in pregnancies complicated with preeclampsia. Methods: The study was designed retrospectively. Between 2016 and 2019, the neonatal results and cord blood gas results of 109 pregnant women who were diagnosed with preeclampsia and 75 nonpreeclamptic randomly selected pregnant women were compared. The preeclampsia group was divided into groups according to amount of proteinuria. SPSS 21.0 statistics program was used, and comparative analysis was carried out. Results: The data of the 109 preeclampsia cases and 75 control groups included in the study were compared, and there was no statistical difference between the fetal cord blood gas parameters between the groups ( p  > 0.05). The median first and fifth minute Apgar scores were found significantly lower in the preeclampsia group compared to the control group (6, 8 and 8, 9, respectively; p  < 0.001). Also, the amount of proteinuria does not alter cord blood gas parameters ( p  > 0.05). Conclusion: Preeclampsia poses a risk for the neonatal period as it reduces the neonatal Apgar scores due to the chronic hypoxic process it creates. However, it was observed that the amount of proteinuria, which is one of the diagnostic criteria, did not affect neonatal results on Apgar scores or fetal cord blood gas parameters.